A longitudinal quantitative analysis of gait in patients with SCA-12. (2021) - Siddique, Ummatul; Choudhury, Supriyo; Chatterjee, Koustav; Rahman, Simin; Bhansali, Sakhi; Mondal, Banashree; Basu, Purba; Kumar, Hrishikesh
Abstract: Introduction: Spinocerebellar ataxia type 12 (SCA 12) is characterized by late onset tremor, ataxia and pyramidal signs. Parkinsonism and cognitive decline may appear with time. It is considered as slowly progressive but temporal evolution of symptoms has not been reported. Method: We report the evolution of symptoms in three SCA12 patients followed over a range of 5–6 years. We focused on the evolution of gait abnormality as it becomes the most disabling symptom as disease advances. Two-dimensional gait parameters were studied using an electronic walkway at various time points to measure objective changes in gait. Result: All patients presented with tremor in the upper extremity at baseline which progressed non-uniformly over the years. Progression of gait variability measures of step length, stance time and step time were also observed. Conclusion: Gait characteristics such as variability may precede clinical gait abnormality and could serve as a sensitive marker for disease progression for better therapeutic intervention in disease management. Future studies with larger sample size should be undertaken to conclusively validate this observation.